Bringing Space into the Classroom: An AR-Integrated E-Book on the Solar System for Students in Elementary School - Dinne Nursyaidah; Diana Rochintaniawati; Nanang Winarno; Rizky Agassy Sihombing (Postgraduate, University of Mataram, 2025)
This study aims to develop an Augmented Reality (AR)-integrated e-book on solar system material to support science education. The development process followed five stages: Analysis, Design, Development, Implementation, and Evaluation. The e-book was validated by experts, yielding a score of 93.36%, indicating it is highly feasible for use in educational settings. Student responses were also assessed, with a score of 88.23%, categorizing the e-book as